8. Validating the alliance "Agrostio-Stipion giganteae" - Rivas-Martínez, Salvador; Fernández-González, Federico (Lazaroa, 2014)
The alliance Agrostio-Stipion giganteae has remained invalid till now, because the various conditions for valid publication have not been simultaneously fulfilled across a relatively long number of works concerning the syntaxon and their subordinate associations.